Gear limitations as a means of fishery conservation - its problems and recommendations. - Mohd, Mohd Ibrahim
Problems in the implementation of present conservation methods in Malaysia are discussed. These methods are primarily based on fishing gear limitations. The unique structure of fixheries in this region particularly Malaysia renders fishing gear limitations only partly effective as a means of conservation. An integrated approach covering closed season, protected areas, selective gears, deep sea fishing,regional cooperation and improved enforcement are recommended. The implementation of these methods in conjunction with effective present regulations can produce an effective conservation system.